A dança que conduz ao céu: as produções discursivas que dão vida à Noite Cubana - Mendes, Maria Lucia Paulino (2010)
In Beberibe, neibourhood placed in the North part of Recife, state of Pernambuco, there is a Hill known as three names Alto do Céu, Alto Santa Terezinha e Alto do Pascoal, where can be found the Bela Vista club, place that twice a month there is a Cuban night, the Cubans or the Cuban family night. This festival has happened since 1992, it gathers men and women from the lower class, most of them senior, to dance in two the songs with Cuban roots , this enjoyable activity is classified this way by them. The organizers do not have any kind of family link even Caribbean dependence. The main objective of this dissertation is analizing the discourse productions of the mentors and participants of this event. The Discourse Analyze (DA) a French proposal made by Michel Pêcheux, and in Brazil, by her disciple Eni Orlandi can be theorical and methodological base in this investigation; these two authors will be the main references of DA in this work. The DA appears in the middle of the 60‟s in the XX century under the linguistic influence, the Psychoanalyzes and the historical materialism, presenting the discourse as a place where the language gets meaning and gives sense to the unconscious person from the history and ideologies. This research involves the observation of the fact, analyze of historical material about the Cuban and discursive analyze of the interview with four women and seven men ages between 45 and 80; during the research the people identities are hidden. The interviews were recorded in audio and latter written and analyzed with theory. The discourse analyses shows the ideological formation that the people has about them, its interlocutor of its interlocutor and enjoyable happening, which became real between the sentence (already Said) and the metaphor (the movement) of the given meaning of the history and there is vocabulary as old/young, poor/rich, afro-descendent or not, gentleman/lady, familiar or not and what is to be Cuban music, Cuban dance, originally Cuban from the Caribbean island and what is to be originally Cuban from Pernambuco. The discursive productions let the party more perfumed by the leaves of cinnamon and calientes rhythm keep existing for 17 unstopped years, making the sill more important, to the club and the people involved